Aerodynamic and aeroelastic characteristics of typical bridge decks equipped with wind barriers at the windward bridge-deck edge. (15th April 2017) - Buljac, Andrija; Kozmar, Hrvoje; Pospíšil, Stanislav; Macháček, Michael
Highlights: Dynamic stability of typical bridge decks equipped with windward wind barrier. Aerodynamic forces and moments modify due to wind barrier. Wind barrier does not considerably increase galloping sensitivity of bridge decks. Wind barrier enhances bridge-deck sensitivity to torsional flutter. Streamlined bridge decks with wind barrier are particularly prone to dynamic instability. Abstract: The present wind-tunnel study focuses on the effects of roadway wind barriers on aerodynamic and aeroelastic characteristics of bridge decks characterized by various aerodynamic shapes of the cross section. Three bridge-deck sections are studied, i.e., streamlined, semi-bluff, and bluff sections. The standard 5 m high (full-scale) wind barrier with 30% porosity is placed at the windward (leading) edge of the bridge-deck sections. Aerodynamic forces and overturning moment are determined at various wind incidence angles. Galloping stability is studied using the quasi-steady theory. Flutter derivatives are determined to evaluate flutter sensitivity of the studied bridge-deck sections with the wind barrier in comparison with the empty bridge-deck sections. The experimental results indicate some important features. In particular, the drag force coefficient is increased for all bridge-deck sections when the wind barrier is in place. This feature is particularly exhibited for the streamlined bridge-deck section. The wind barrier alters the trends and values of the lift force coefficient, while the influence of the wind barrier on the pitch moment is particularly exhibited for positive wind incidence angles, which is characteristic for all bridge-deck sections. The wind barrier does not influence the galloping sensitivity of the studied bridge-deck sections, while it deteriorates their dynamic stability with respect to torsional flutter.